Itinerários da produção intelectual de Antenor de Veras Nascentes na comunicação científica - Silva, Ana Maria da (2012)
Research on the intellectual production of Antenor de Veras Nascentes, Brazilian professor and researcher, focusing on the aspects of Scientific Communication and on parameters of productivity in Science. The analysis was based on the author s life and production, in his biographical and bibliographical characteristics. The Colegio Pedro II and the Brazilian cultural life at his lifetime was the scenario. The analysis allowed to classify the documental typology of Antenor Nascentes as books, books chapters, national and interational scientific papers, and also translations and dictionaries. The latter were the central focus of his studies and research, which was manifested by the first Etimological Dictionary. The international letters received by him were the source for the identification of the his network, as a way to understand his impact outside Brazil. The research results point to multiple aspects that show Antenor Nascentes s work with a pionnering character, driven by his innovative thinking and its importance, specially in the fields of Linguistics, Phylology and Dialectology, that heavily influenced today s Linguistics. Antenor proposed paths that seem to transcend the common Brazilian thinking of his time